2004
DOI: 10.1023/b:jarg.0000027016.65749.ad
|View full text |Cite
|
Sign up to set email alerts
|

Use of Stimulated Serum Estradiol Measurements for the Prediction of Hyperresponse to Ovarian Stimulation in in Vitro Fertilization (IVF)

Abstract: Purpose : In ovarian stimulation an exaggerated ovarian response is often seen and is related to medical complications, such as ovarian hyperstimulation syndrome (OHSS), and increased patient discomfort. If it were possible to identify hyperresponders at an early stage of the stimulation phase, adaptation of the stimulation protocol would become feasible to minimize potential complications. Therefore, we studied the usefulness of measuring stimulated serum estradiol (E 2 ) levels in predicting ovarian hyperres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…Our results showed that P4 attenuated the negative regulatory effect of E 2 on integrin β3. It is known that P4 can inhibit the proliferative effect of E 2 on endometrium by down-regulating the expression of E 2 receptors [24]. While this antagonistic effect of P4 on E 2 is generally believed to influence the completeness of the secretory transformation of endometrium [20]; during the embryo implantation process, a high E 2 level will cause the window of uterine receptivity to rapidly close [1].…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that P4 attenuated the negative regulatory effect of E 2 on integrin β3. It is known that P4 can inhibit the proliferative effect of E 2 on endometrium by down-regulating the expression of E 2 receptors [24]. While this antagonistic effect of P4 on E 2 is generally believed to influence the completeness of the secretory transformation of endometrium [20]; during the embryo implantation process, a high E 2 level will cause the window of uterine receptivity to rapidly close [1].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, serum estradiol concentrations were also significantly associated with OHSS (17)(18)(19)(20)(21)(22)(23)(24)33). In the majority of these studies, the mean estradiol value in patients with OHSS was >3,500 pg/mL.…”
Section: Ovarian Stimulation Parameters (Follicles Oocytes Estradiol)mentioning
confidence: 95%
“…Many investigators have shown that an elevated concentration of estradiol during ovarian stimulation constitutes a risk factor for OHSS [3,5,22,23,35,37,38]. However, as mentioned above, patients presented with serum estradiol of ≥6000 pg/ml and/or more than 30 follicles, or where coasting or other preventive measures for managing OHSS had been applied, were not included in the present study cohort.…”
Section: Discussionmentioning
confidence: 99%